Doxorubicin-induced oxidative stress injury: The protective effect of kumiss on cardiotoxicity - Yilmaz, Seval; Kaya, Emre; Yonar, Harun; Mendil, Ali Sefa (Hellenic Veterinary Medical Soc, 2022)
Doxorubicin (DOX), which is used in cancer treatment, is an effective chemotherapy agent with many side effects. Cardiotoxicity, on the other hand, is the most important side effect, and it has pushed us to work with kumiss, an alcoholic beverage made from mare's milk, rich in fermentates, trace elements, antibiotics, vitamins, ethyl alcohol, lactic acid and carbonic acid.The aim of this study was to investigate the effect of kumiss on cardiotoxicity caused by DOX. Twenty-eight Wis-tar-Albino male rats were divided into 4 groups: There was no intervention in the first group (control). The second group received 2 ml/kg/day of kumiss by gavage needle for 7 days, a single dose of 20 mg/kg, intraperitoneal DOX to the third group, and kumiss+DOX to the fourth group. Kumiss application was started 7 days before DOX admin-istration and continued for 7 days. On the 7th day of kumiss application, DOX was administered intraperitoneally. The malondialdehyde (MDA), reduced glutathione (GSH) levels and antioxidant enzymes such as catalase (CAT), gluta-thione peroxidase (GSH-Px), superoxide dismutase (SOD), glucose-6-phosphate dehydrogenase (G6PD) and gluta-thione-S-transferase (GST) activities were determined in order to determine their effectiveness in the pathogenesis of cardiotoxicity in cardiac and blood tissues.When the DOX group was compared with the control group, an increase in MDA (p<0.001, p<0.001) and GSH (p<0.001, p=0.002) levels and a decrease in CAT (p=0.001, p<0.001), GSH-Px (p<0.001, p<0.001), G6PD (p<0.001, p=0.001) and GST (p=0.003) activities were found, and no statistically significant difference was found in SOD ac-tivity. Histopathologically, degeneration, necrosis, hemorrhage and oedema were observed in the DOX administered group. When compared with the group treated with DOX, it was observed that MDA, GSH levels and antioxidant enzyme activities reached the control group values in the group administered kumiss with DOX.In conclusion, it was determined that an increase in lipid peroxidation products and a decrease in antioxidant enzymes may play a role in the pathogenesis of DOX-induced cardiotoxicity, a potent chemotherapeutic drug, and it has been shown that protects against DOX-induced oxidative damage.
Keywords: Doxorubicin; cardiotoxicity; kumiss; malondialdehyde; antioxidant